Recommendations for clinical staging (cTNM) of cancer of the esophagus and esophagogastric junction for the 8th edition AJCC/UICC staging manuals. Issue 8 (1st December 2016) - Rice, Thomas W.; Ishwaran, Hemant; Blackstone, Eugene H.; Hofstetter, Wayne L.; Kelsen, David P.; Apperson-Hansen, Carolyn; ,
Summary: We report analytic and consensus processes that produced recommendations for clinical stage groups (cTNM) of esophageal and esophagogastric junction cancer for the AJCC/UICC cancer staging manuals, 8th edition. The Worldwide Esophageal Cancer Collaboration (WECC) provided data on 22, 123 clinically staged patients with epithelial esophageal cancers. Risk-adjusted survival for each patient was developed using random survival forest analysis from which (1) data-driven clinical stage groups were identified wherein survival decreased monotonically and was distinctive between and homogeneous within groups and (2) data-driven anatomic clinical stage groups based only on cTNM. The AJCC Upper GI Task Force, by smoothing, simplifying, expanding, and assessing clinical applicability, produced (3) consensus clinical stage groups . Compared with pTNM, cTNM survival was "pinched, " with poorer survival for early cStage groups and better survival for advanced ones. Histologic grade was distinctive for data-driven grouping of cT2N0M0 squamous cell carcinoma (SCC) and cT1-2N0M0 adenocarcinoma, but consensus removed it. Grouping was different by histopathologic cell type. For SCC, cN0-1 was distinctive for cT3 but not cT1-2, and consensus removed cT4 subclassification and added subgroups 0, IVA, and IVB. For adenocarcinoma, N0-1 was distinctive for cT1-2 but not cT3-4a, cStage II subgrouping was necessary (T1N1M0 [IIA] and T2N0M0 [IIB]), advanced cancers cT3-4aN0-1M0 plus cT2N1M0 comprised cStage III, and consensus added subgroups 0, IVA, and IVB. Treatment decisions require accurate cStage, which differs from pStage. Understaging and overstaging are problematic, and additional factors, such as grade, may facilitate treatment decisions and prognostication until clinical staging techniques are uniformly applied and improved.